2017
DOI: 10.3390/ijgi7010003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Seasonality on Urban Land-Cover Mapping Using Multi-Season Sentinel-1A and GF-1 WFV Images in a Subtropical Monsoon-Climate Region

Abstract: The objective of this research was to investigate the impact of seasonality on urban land-cover mapping and to explore better classification accuracy by using multi-season Sentinel-1A and GF-1 wide field view (WFV) images, and the combinations of both types of images in subtropical monsoon-climate regions in Southeast China. We obtained multi-season Sentinel-1A and GF-1 WFV images, as well as the combinations of both data, by using a support vector machine (SVM) and a random forest (RF) classifier. The backsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Studies that use S-2 time series focus on one or a few specific land cover classes, usually on homogeneous agricultural or forested landscapes located in the same climatic region [28][29][30][31][32][33][34]. Use of S-1 data has been limited to combining them with S-2 or Landsat data, which increases classification accuracy [35][36][37][38][39]. Hence, the use of S-1 time series alone for mapping land cover classes has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that use S-2 time series focus on one or a few specific land cover classes, usually on homogeneous agricultural or forested landscapes located in the same climatic region [28][29][30][31][32][33][34]. Use of S-1 data has been limited to combining them with S-2 or Landsat data, which increases classification accuracy [35][36][37][38][39]. Hence, the use of S-1 time series alone for mapping land cover classes has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…While we have shown that lower error rates may not result in more stable predictions, using all available data for a model will likely improve accuracy and result in a more accurate thematic map. Other studies have reported increases in classification accuracy in RF models with the addition of combined seasonal images, hyperspectral data, lidar images, radar (synthetic aperture radar, SAR) images, and ancillary geographical data such as elevation and soil types (Corcoran et al, 2013;Pu et al, 2018;Shi et al, 2018;Xia et al, 2018;Yu et al, 2018;Zhou et al, 2018). RF models have the ability to handle highly dimensional correlated data and data combined from multiple different data sources across different temporal scales; however, one disadvantage to using nonparametric classifiers such as RF and decision trees is that they require a large number of observations to accurately estimate the mapping function (James et al, 2014).…”
Section: Random Forest Model Resultsmentioning
confidence: 99%
“…The SAR image used in this study was Sentinel-1A that was downloaded from the ESA (European Space Agency), whereas the optical data was Landsat-8 OLI that was downloaded from the USGS (US Geological Survey). Designed by the ESA, Sentinel-1 is composed of two satellite constellations, including Sentinel-1A and Sentinel-1B [33]. The Sentinel-1A carries a C-band SAR imaging instrument that provides four imaging modes.…”
Section: Remote Sensing Variablesmentioning
confidence: 99%